RUPTURE OF THE UTERUS ALONG THE SCAR DURING PREGNANCY - Нонна Марковна Шибельгут; Наталья Анатольевна Батина; Алена Васильевна Иванникова; Полина Андреевна Овчарова; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Кира Борисовна Мозес; Вадим Гельевич Мозес (The Publishing House Medicine and Enlightenment, 2023)
A scar on the uterus occurs more often due to the delivery of women by CS surgery in the anamnesis (78-84 %). Maternal mortality is mainly associated with uterine rupture (22-75/10000), bleeding, thromboembolic and infectious complications. The frequency of endometritis in the postpartum period increases by 1 % (289/10000 compared to 180/10000 during elective cesarean section). With planned CS, the risk of thromboembolic complications increases 3.8 times, uterine rupture in subsequent pregnancies - 42 times, abdominal pain - 2 times, bladder injury - 36 times. This publication is devoted to the delivery of a woman with a complete rupture of the uterus along the scar after previous cesarean sections.